ANALISA EFEKTIVITAS HEAT EXCHANGER OIL COOLER SEBELUM DAN SESUDAH MAINTENANCE - Aziz Masyhuri; Angky Puspawan; Agus Suandi (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2022)
MUSI PLTA is one of the state-owned companies engaged in Hydroelectric Power Generation, MUSI PLTA is one of the largest power plants in Bengkulu Province, which is also a power plant in several provinces on the island of Sumatra. Air power plants consist of many interrelated components which then convert the potential energy of the air into mechanical energy which is then transformed into electrical energy. One of the most important components of this plant is the oil cooler. The oil cooler is a heat exchanger that functions to cool the oil that will be used as a thrust bearing on the generator. This oil cooler has a shell and tube type where two types of fluids flow separately with a two pass heat exchanger type. The effectiveness of the oil cooler unit 1 UL PLTA MUSI on conditions before and before treatment was obtained from the calculation of the effectiveness value. In the pre-maintenance condition, the effectiveness value was 9.947089947 %, while in the pre-maintenance condition the effectiveness value was 13.03 %.